PENGARUH KECAKAPAN KOMUNIKASI DAN MEMOTIVASI GURU PAI TERHADAP MOTIVASI BELAJAR PESERTA DIDIK ERA PANDEMI COVID-19: Studi Kasus di Kelas XI SMAN 1 Bojongsoang Kabupaten Bandung - Tika Kartika Sari; Asep Fathurrohman; Helmawati (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2022)
The learning process, which usually occurs face-to-face in schools, was suddenly forced to switch to online learning to prevent the spread of the coronavirus. This kind of situation and condition greatly affects the learning motivation of students, many of the students have decreased their learning motivation. This study wants to find out whether there is an influence on communication skills and motivating PAI teachers on the learning motivation of students in the pandemic era, where at this time learning is carried out online and how much influence it has. This research method uses a quantitative approach with a survey method using an online questionnaire in the form of a g-form. The results of the study are: (1) there is an influence between the communication skills of PAI teachers on the learning motivation of students in the Covid-19 pandemic era (2) there is an influence between the skills of motivating PAI teachers on the learning motivation of students in the Covid-19 pandemic era. (3) there is a simultaneous influence between communication skills and motivating PAI teachers on the learning motivation of students during the Covid-19 pandemic era, this is indicated by the value of the double correlation coefficient of 0.650 or the coefficient of determination of 42.3%.